The Struggle for Sufficient Housing in Santa Clara Countuy - Musallam, Robert (2010)
This study examined the role systemic racism plays in shaping people's ability to acquire sufficient housing in Santa Clara County. The purpose of this study was to identify historical and contemporary forms of institutional racism through the narratives of residents or former residents of the San Jose Family Homeless Shelter [SJFS] in San Jose, California. Of particular interest is evidence of housing discrimination and what Neubeck and Cazenave (2001) call welfare racism. Clients of the SJFS represent those directly affected by welfare reform and least protected from oppressive housing policies or practices. Through semi-structured open-ended interviews with former residents of the SJFS and several key informants, the process of how obtaining housing manifests on the ground, identifying the barriers to finding sufficient housing, and discussions on the respondents' inability to find units that fit their own definitions of sufficient housing were explored. The paper concludes by suggesting that these narratives identify a need to explore sufficient housing more specifically. Furthermore, the need to inform our collective efforts to resist systemic racism and create more equitable housing policies/practices in Santa Clara County is critical and must be addressed